2022
DOI: 10.3389/fncel.2022.831061
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glutamate Transport Increases Arteriole Diameter in vivo: Implications for Neurovascular Coupling

Abstract: In order to meet the energetic demands of cell-to-cell signaling, increases in local neuronal signaling are matched by a coordinated increase in local blood flow, termed neurovascular coupling. Multiple different signals from neurons, astrocytes, and pericytes contribute to this control of blood flow. Previously, several groups demonstrated that inhibition/ablation of glutamate transporters attenuates the neurovascular response. However, it was not determined if glutamate transporter activation was sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…Jackson and colleagues showed that Ca 2+ influx by NCX in response to glutamate transporters‐dependent Na + influx is the main source of Ca 2+ transients in perisynaptic astrocyte processes in organotypic hippocampal slices (Jackson & Robinson, 2015). In addition, the same group found that treatment with glutamate or other glutamate transporter substrates increases blood flow (Jackson et al, 2022), in a process known as neurovascular coupling. This response was partially blocked by inhibitors of the reverse mode of NCX (Jackson et al, 2022).…”
Section: Glutamate Transporters As Transducer Molecules: Role Of the ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Jackson and colleagues showed that Ca 2+ influx by NCX in response to glutamate transporters‐dependent Na + influx is the main source of Ca 2+ transients in perisynaptic astrocyte processes in organotypic hippocampal slices (Jackson & Robinson, 2015). In addition, the same group found that treatment with glutamate or other glutamate transporter substrates increases blood flow (Jackson et al, 2022), in a process known as neurovascular coupling. This response was partially blocked by inhibitors of the reverse mode of NCX (Jackson et al, 2022).…”
Section: Glutamate Transporters As Transducer Molecules: Role Of the ...mentioning
confidence: 99%
“…In addition, the same group found that treatment with glutamate or other glutamate transporter substrates increases blood flow (Jackson et al, 2022), in a process known as neurovascular coupling. This response was partially blocked by inhibitors of the reverse mode of NCX (Jackson et al, 2022). We found that GLT1‐ and GLAST‐dependent Ca 2+ influx, mediated by NCX, induces the morphological aspects of oligodendrocyte maturation through the activation of the actin‐binding domain of calcium/calmodulin‐dependent protein kinase II beta (CaMKIIβ) (Martinez‐Lozada et al, 2014).…”
Section: Glutamate Transporters As Transducer Molecules: Role Of the ...mentioning
confidence: 99%